Health and safety risk of female trafficking in Nigeria: implications for border security transformation (2019)
Human trafficking has become one of the most worrisome phenomenon and Nigeria acts as origin, transit and destination point for trafficking. The country is ranked as a third tier country in 2018 Global Terrorism Report. Weak border control and governance has been reported to play significant role in promoting trafficking in persons globally, especially in Nigeria. The disadvantageous stereotype attributed to the female gender is another contributory factor and it is more pronounced in the African highly patriarch society. Trafficking is a gendered phenomenon that has women as the most vulnerable group with adverse health effect. The vulnerability of women in trafficking is further portrayed in large body of evidence which demonstrates that trafficking has deleterious effect on psychological, social, physical and physiological health of its victims. This paper attempts to put the gender dimension of trafficking into perspective in relation to its adverse health effect on women and girl children. Addressing the issue through effective border control as a strategy to combating and preventing female trafficking in Nigeria was also discussed.